POLA PERJALANAN KERJA PEDAGANG SAYURAN (KASUS PADA WANITA PEDAGANG SAYURAN DI PASAR UNGARAN KABUPATEN SEMARANG) (Faculty of Social Science, Universitas Negeri Semarang, 2008)
Women participation at public sectors are more and more large. Those cases are happened at rural andurban area. The public sector which gives much opportunities for women to do is trade sector, because thissector is not too require specifically for skill and the allocation time for this sector is flexible. The questionsin this research are: 1) where are the vegetable women trader come from? 2) where are the vegetablecommodities come from? 3) are side destination by vegetable women trader beside to the market? 4) whatare the facility of transportation used by vegetable women trader? 5) how are the pattern of the work tripsformed? The result of this research are: 1) the area origin from vegetable women trader at Ungaran Marketare Semarang Regency (70.36%), Semarang City ( 25.95%) and Salatiga City (3.70%); 2) the area originfrom vegetable commodities are Semarang Regency (Sumowono, Ambarawa, Ungaran, Getasan), andSemarang City (Gunungpati, Mijen, dan Banyumanik); 3) the transportation infrastructure and facilitiesto service vegetable women trader to do to Ungaran Market are enough; 4) the time allocation from thevegetable women trader’s work trips are 8 – 13 hours; 5) the pattern of vegetable women trader’s worktrips at Ungaran Market are 6 (six) types.Keywords : Women trader, pattern of work trips